Critical Discourse Analysis of President Joko Widodo’s Welcoming Speech at 42nd ASEAN Summit - Syafri, Mohamad; Ghina, Inas (Universitas Pamulang, 2024)
The ASEAN Summit has become an interesting momentum and is in the spotlight because the views and attitudes of Southeast Asian leaders will be greatly reflected in the event. The 42nd ASEAN Summit is an attractive momentum considering Indonesia's status as the current Chairman of ASEAN, that this activity was also carried out in post-COVID-19 Pandemic conditions and Timor-Leste's first involvement as a candidate for a new ASEAN member. Focusing on the welcoming speech by President Joko Widodo at the Summit, this study uses a descriptive qualitative method using the Critical Discourse Analysis (CDA) model developed by Norman Fairclough. This study conducts discourse analysis using three dimensions: text, discursive, and sociocultural analysis. The results of the analysis show that textually the speech delivered by President Joko Widodo uses the words 'I' and 'ASEAN' repeatedly. The term 'I' is generally in the function of hosting activities, and 'ASEAN' indicates a collective effort. Modality in the speech is also used to reinforce the vision of ASEAN. The socio-cultural analysis shows that the speech delivered by President Joko Widodo has characteristics to emphasize the current condition in the form of internal and external challenges. On the other hand, ideologically, President Joko Widodo stresses the message of exploring the potential in accordance with ASEAN's vision.